SETIATI SURASTO DALAM PERJUANGAN BURUH PEREMPUAN PADA 1940AN-1960AN - WULANDARI, AYU (Handep: Jurnal Sejarah dan Budaya, 2023)
This research discusses the views and roles of Setiati Surasto in improving the fate of women labour between the 1940s and 1960s. This study stems from companies’ or employers’ discrimination that always considers female labour as cheap labour from time to time. Women labour were seen as unskilled workers, feasibly exploited and not appreciated. Consequently, women labour experiences discrimination in various forms, ranging from wages to violations of their rights. This study used historical research methods in which newspapers and magazines were primary sources. The findings indicate that the inequality that they experience generates women’s agency and activism. Setiati Surasto was one of the activists who voiced her views on equality and welfare for women labour through writing and direct action. This research has filled the gaps in Indonesian historiography, especially by presenting the biography of a women’s labour activist during the early period of Indonesian independence.